APPLICATION TO MAKE ANIMATED INTERACTIVE MULTIMEDIA USING MACROMEDIA FLASH MX 2004 - Harry Zulfikar; Yudi Irawan Chandra, SKom, MMSI (Jurnal Sistem Informasi, 2008)
Scientific writing is about an Interactive Applications To Create Animations Multimedia. This application is made to provide methods which can facilitate the learning process and create a multimedia animation. In this scientific writing, Interactive Applications To Create Animations Multimedia author using Macromedia Flash MX 2004 that can support the presentation of the learning method in this application include the use of text, images, motion and accompanied by a voice that can be expected to attract more users to create animated multimedia learning.